Sexuality Comparison in Novel Eleven Minutes With Tuhan Izinkanlah Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah - Misnawati Misnawati; Lazarus Linarto; Petrus Poerwadi; Alifiah Nurachmana; Albertus Purwaka; Patrisia Cuesdeyeni; Paul Diman; Yuliati Eka Asi (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
The purpose of this research is to describe the theme of sexuality in the main character, Maria (novel